Hadith #3822 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Bakr bin Swad'h bin Thmamh بكر بن سوادة بن ثمامة (Sunan Abi Dawud)
He who eats garlic or onion must keep away from us. Or he said: must keep away from our mosque or must sit in his house. A dish containing green vegetables was brought to him, and noticing that it had an odour he asked (about it). He was told that it contained some vegetables. He then said: Bring it near, to one of his companion who was with him. When he saw it, he abominated eating it, and said: eat for I hold intimate converse with one with whom you do not. Ahmad b. Salih said: Ibn Wahb explai
Grade: Sahih